2023
DOI: 10.1136/bmjopen-2022-069579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dementia on all-cause mortality in hip fracture surgery: a retrospective study on a nationwide Korean cohort

Abstract: ObjectivesWe aimed to evaluate the effect of dementia on the 1-year all-cause mortality in elderly patients who underwent hip fracture surgery, using a nationwide cohort in Korea.Design, setting, and participantsThis was a nationwide, retrospective study. Elderly patients (≥60 years) with and without dementia who underwent hip fracture surgery between January 2005 and December 2012 were distinguished using the data from the Korean National Health Insurance Service-Senior cohort.InterventionsNone.Primary and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Specifically, Bai et al found that mortality of dementia patients with hip fractures postoperatively is 12% at 30day follow-up and 45% at more than 1year follow-up 27 . Similarly, other studies show that hip fracture patients with dementia have an increase in mortality rate between 23% and 67% 21,22,26 .…”
Section: Morbidity and Mortality Of Hipmentioning
confidence: 59%
See 1 more Smart Citation
“…Specifically, Bai et al found that mortality of dementia patients with hip fractures postoperatively is 12% at 30day follow-up and 45% at more than 1year follow-up 27 . Similarly, other studies show that hip fracture patients with dementia have an increase in mortality rate between 23% and 67% 21,22,26 .…”
Section: Morbidity and Mortality Of Hipmentioning
confidence: 59%
“…When analyzing the number of hip fracture patients who had a preincident diagnosis of dementia, studies suggest that between 10.5% and 29.7% of patients who undergo hip fracture surgery have a preoperative diagnosis of dementia 12,[22][23][24] . These studies, however, only included patients who underwent surgery to repair a hip fracture.…”
Section: Morbidity and Mortality Of Hipmentioning
confidence: 99%
“…Hip fracture among older adults often results in decreased independence and quality of life . Surgery is a potential treatment option, yet people living with dementia undergoing this operation experience higher mortality, delirium, and postoperative complications, with a consequent greater loss of mobility compared with persons without cognitive difficulties . Much less is known about what happens to patients with hip fractures who do not have surgery.…”
Section: Introductionmentioning
confidence: 99%